2022
DOI: 10.3390/geriatrics7020038
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-Targeted Atherosclerotic Risk Reduction in Older Adults: A Review

Abstract: Aggressive lipid-lowering lifestyle modifications and pharmacologic therapies are the cornerstones of the primary and secondary prevention of atherosclerotic cardiovascular disease events. While statins are highly effective, inexpensive, and generally well-tolerated medications, many clinicians and patients express uncertainty regarding the necessity of statin treatment in older adults. Citing concerns such as polypharmacy, muscle symptoms, and even potential cognitive changes with statins, many patients and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“…Shown in our analyses, statin utilization is low among older adults for primary prevention. Medical provider inertia in using statins, due to myalgias and various factors in older adults is a well-documented phenomenon [ 26 , 27 ], however, based on our results, this intervention is likely needed given reduction in ASCVD events. While myalgias are a common reason for statin discontinuation or lack of initiation, it has been shown that many patients experience myalgias with similar frequencies whether on a statin or placebo indicating that this may be a psychological reaction [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shown in our analyses, statin utilization is low among older adults for primary prevention. Medical provider inertia in using statins, due to myalgias and various factors in older adults is a well-documented phenomenon [ 26 , 27 ], however, based on our results, this intervention is likely needed given reduction in ASCVD events. While myalgias are a common reason for statin discontinuation or lack of initiation, it has been shown that many patients experience myalgias with similar frequencies whether on a statin or placebo indicating that this may be a psychological reaction [28] .…”
Section: Discussionmentioning
confidence: 99%
“…Many major guidelines rely on having a discussion between the patient and provider about the initiation of a statin in individuals older than 75 years of age [1] . Lack of concrete guideline directions on statin use in older adults for primary prevention is likely due to the paucity of evidence and lack of recruitment of the aging adults in randomized controlled trials [ 27 , 31 ]. Our work can add to the literature to support clear guidelines for statin use among at least high-risk older adults.…”
Section: Discussionmentioning
confidence: 99%